ON THE ISSUE OF EXCESSIVE INDEBTEDNESS (Globalization and Business, 2018)
Excessive indebtedness, or the “overproduction” of credits, is a feature of the modern credit system. Its results are commonly encountered in the local, regional or global economies. It appears before us as a cause of a severe financial and economic crisis. Despite the regulation methods using in the modern «mainstream» theory and practice to address the existing problems, it is still posing the new challenges for the regulatory institutions, beyond the focus of which, one main issue remains permanently: how the“overproduction” of credits is created in demand economics(but not in need economics)on such scarce resources as money and savings. Over the past few years, in the composition of bank loan portfolio of the Georgian banking sector, there has been significantly strengthened and increased the share of loans to natural persons, while the share of the local economy in GDP is almost non-existent and stays in the low single digits.Obviously, the process was observed by the National Bank,and based on the theoretical foundations of its functioning it has adopted a new regulatory norm.The article dwells on studying, the process of the“overproduction” of credits and the causes of the causes, as well as the main aspects of a new regulation set out by the National Bank of Georgia and the expected outcomes, and the relevant conclusions have been made.